2022
DOI: 10.1007/s40333-022-0022-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the growing-maize canopy and irrigation characteristics on the ability to funnel sprinkler water

Abstract: Stemflow is vital for supplying water, fertilizer, and other crop essentials during sprinkler irrigation. Exploring the spatial and temporal variations of crop stemflow and its influencing factors will be essential to preventing soil water and nutrient ion's migration to deeper layers, developing, and optimizing effective sprinkler irrigation schedules. Based on the two-year experimental data, we analyzed the variation patterns (stemflow amount, depth, rate, and funneling ratio) of maize stemflow during the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Raina et al 12 found that drip irrigation besides giving a saving of 54% irrigation water resulted in 40% higher fruit yield compared with the surface irrigation. Due to the different irrigation amount and irrigation intensity of different water-saving irrigation techniques 13 , irrigation method directly affects the growth and development of maize 14 . Qin et al 15 research results show that under different irrigation methods, drip irrigation not only achieve the role of water saving, but also on the growth of maize can play a role in increasing production.…”
Section: Introductionmentioning
confidence: 99%
“…Raina et al 12 found that drip irrigation besides giving a saving of 54% irrigation water resulted in 40% higher fruit yield compared with the surface irrigation. Due to the different irrigation amount and irrigation intensity of different water-saving irrigation techniques 13 , irrigation method directly affects the growth and development of maize 14 . Qin et al 15 research results show that under different irrigation methods, drip irrigation not only achieve the role of water saving, but also on the growth of maize can play a role in increasing production.…”
Section: Introductionmentioning
confidence: 99%
“…Raina et al (1999) found that drip irrigation besides giving a saving of 54% irrigation water resulted in 40% higher fruit yield compared with the surface irrigation. Due to the different irrigation amount and irrigation intensity of different water-saving irrigation techniques (Michel and Kerloch 2017), irrigation method directly affects the growth and development of maize (Zhu et al 2022). Many scholars have done a lot of research on the effects of different irrigation methods on maize growth.…”
Section: Introductionmentioning
confidence: 99%